Recurrent BRAF Gene Rearrangements in Myxoinflammatory Fibroblastic Sarcomas, but Not Hemosiderotic Fibrolipomatous Tumors - Yu‐Chien Kao; Valentina Ranucci; Lei Zhang; Yun-Shao Sung; Edward A. Athanasian; David Swanson; Brendan C. Dickson; Cristina R. Antonescu (2017)
Myxoinflammatory fibroblastic sarcoma (MIFS) is a low grade soft tissue sarcoma with a predilection for acral sites, being associated with a high rate of local recurrence but very infrequent distant metastases. Although a t(1;10) translocation resulting in TGFBR3-MGEA5 fusion has been reported as a recurrent genetic event in MIFS, this abnormality is seen only in a subset of cases. As no studies to date have investigated the spectrum of alternative genetic alterations in TGFBR3-MGEA5 fusion negative MIFS, we undertook a genetic analysis of this particular cohort for further molecular classification. Triggered by an index case occurring in the finger of a 37-year-old female and harboring a novel TOM1L2-BRAF fusion by targeted RNA sequencing we investigated potential recurrent BRAF abnormalities by screening a large group of 19 TGFBR3-MGEA5 fusion negative MIFS by fluorescence in situ hybridization. There were 6 (32%) additional MIFS with BRAF genetic abnormalities, including 5 gene rearrangements and one showing BRAF amplification. Interestingly, VGLL3 amplification, a recurrent genetic abnormality coexisting with t(1;10) in some MIFS, was also detected by fluorescence in situ hybridization in 4/6 (67%) BRAF-rearranged MIFS, but not in the BRAF-amplified case. Up-regulated VGLL3 mRNA expression was also demonstrated in the index case by RNA sequencing. The 7 BRAF-rearranged/amplified MIFS arose in the fingers (n=3), and 1 each in wrist, forearm, foot, and knee, of adult patients (36 to 74 y; M:F=4:3). The histologic spectrum ranged from predominantly solid growth of plump histiocytoid to epithelioid tumor cells with focal myxoid change to a predominantly myxoid background with scattered tumor cells. Varying degree of inflammatory infiltrates and large tumor cells with virocyte-like macronucleoli were observed in most cases. Immunohistochemical stains of phosphorylated ERK, a downstream effector of BRAF activation, were positive in all 4 cases tested (2 diffuse strong, 2 focal strong). Unlike t(1;10), BRAF rearrangements were only found in MIFS but not in 6 hemosiderotic fibrolipomatous tumor (HFLT) lacking TGFBR3-MGEA5 fusions (including 2 pure HFLT, 2 hybrid HFLT-MIFS, and 2 associated with pleomorphic hyalinizing angiectatic tumors).